Enhancing Cloud and Big Data Systems for healthy Food and Nutrition Information Systems Practice: A Conceptual Study - Paul, P.K.; Aithal, P.S.; Bhuima, A. l (International Journal of Scientific Research in Biological Sciences, 2017)
Cloud Computing is a kind of virtualization technology based on internet. In cloud computing, central remote server plays an important role for healthy data management and applications. It offers handsome efficiency in the field of Computing as well as Information Technology for providing centralized storage, money, processing, and bandwidth. Thus regardless of the size of the institute (i.e. big or small) there is no additional requirement for the establishment of own as well separate IT infrastructure for more and higher business units. Networking Technology and Internet Technology play a vital role in the establishment of cloud computing in different settings. Today it is treated as an emerging technology among the other applied Information Science & Technology. India is strong as well as developed in many senses with a good amount of educational institutes for diverse sectors and community. Cloud computing is applicable in a different field in the current scenario, such as Education, Public Administration, Business & Commerce, Health, and Medicine etc. Interestingly, cloud computing may be applicable in the field of Food and Nutrition. This is a conceptual paper deal with cloud computing related aspects which include benefits, advantages, challenges, and issues. Moreover, the paper also talks about cloud computing applications in different and diverse areas of Food Science, Nutrition and Dietetics. Further, the paper discusses some of the contemporary and future challenges to build Cloud Computing based Food Information Systems.